HIV and AIDS knowledge, attitudes and practices of construction workers : a comparative study of rural and urban based construction workers in Kwazulu-Natal - Mabika, Mandisi Siphiwengesihle (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.